Influence of the concentration of Sb2O3 and the viscosity of the precursor solution on the electrical and optical properties of SnO2 thin films produced by the Pechini method - Bernardi, MIB; Soledade, L. E.; Santos, I. A.; Leite, E. R.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Elsevier B.V., 2002)
SnO2:Sb multi-layer coatings were prepared by the Pechini method. An investigation was made of the influence of the concentration of Sb2O3 and the viscosity of the precursor solution on the electrical and optical properties of SnO2 thin films. The use of a multi-layer system as an alternative form of increasing the packing and. thus. decreasing porosity proved to be efficient, decreasing the system's resistivity without altering its optical properties. (C) 2002 Elsevier B.V. B.V. All rights reserved.
Keywords: thin films; the Pechini method; SnO2 : Sb; optical and electrical properties